Analisa Angka Koefisien Kekasaran Manning Pada Saluran Terbuka Akibat Vegetasi - Saiful Arfaah; Ruslan Hidayat; Iwan Cahyono (Nucleus Journal, 2024)
One of the conductors of water flow is an open channel, which we often encounter for irrigation and drainage purposes. Flow velocity (V) in an open channel depends on several parameters, namely longitudinal slope, cross-sectional geometric elements and obstacles that occur along the channel. Longitudinal slopes and geometric elements can be directly measured in the field or planned. The resistance value varies greatly depending on several factors, for example the material used for the body of the channel and other obstacles such as the presence of vegetation along the channel (vegetation). The resistance value in the channel is expressed by a resistance coefficient number such as the Chezy, Strickler and Manning resistance coefficient. This research aims to determine the resistance coefficient value in open channels, which is influenced by vegetation. The channel roughness coefficient used is the Manning roughness coefficient (n). Observations were carried out on a prototype open channel made from river stone masonry with dimensions of base width = 0.3 m, height = 0.5 m and channel slope = 1 : 1 with vegetation variations of 0%, 25%, 50%, 75%, and 100% of the channel length. Flow velocity was measured using a Currentmeter with 5 measurements for each variation in vegetation percentage. From the results of the analysis and changes, it was found that there was a slowdown in the flow velocity along with an increase in the percentage of vegetation relative to the length of the channel. For normal channels/without vegetation, the value "n" = 0.025 is obtained which corresponds to Manning's "n" value for stone masonry channels. Meanwhile, for the percentage of growth of 25%, 50%, 75% and 100%, there is an increase in the "n" value respectively as follows; 0.031, 0.043, 0.058, and 0.062